UNCOVERING THE ROLE OF SURFACE-ATTACHED AG NANOPARTICLES IN PHOTODEGRADATION IMPROVEMENT OF RHODAMINE B BY ZNO-AG NANORODS - Em, Svetlana; Yedigenov, Mussa; Khamkhash, Laura; Atabaev, Shanazar; Molkenova, Anara; Poulopoulos, Stavros G.; Atabaev, Timur Sh. (Nanomaterials, 2022)
ZnO nanorods decorated with metal nanoparticles have sparked considerable interest in recent years thanks to their suitability for a wide range of applications, such as photocatalysis, photovoltaics, antibacterial activity, and sensing devices. In this study, we prepared and investigated the improved solar-light-assisted photocatalytic activity of ZnO nanorods (NRs) decorated with Ag nanoparticles (NPs) using a conventional rhodamine B (RB) dye as a model water pollutant. We showed that the presence of Ag NPs on the surface of ZnO NRs significantly increases the degradation rate of RB dye (~0.2432 min􀀀1) when compared to bare ZnO NRs (~0.0431 min􀀀1). The improved photocatalytic activity of ZnO-Ag was further experimentally tested using radical scavengers. The obtained results reveal that ˙OH and ˙O2 􀀀 radicals are main active species involved in the RB dye photodegradation by ZnO-Ag NRs. It was concluded that efficient charge separation plays a major role in photocatalytic activity improvement.
Keywords: Type of access: Open Access; ZnO nanorods; Ag nanoparticles; photodegradation; photocatalytic activity; radical scavengers; rhodamine B